Electronic Supply Chain Management Model for Monitoring Plant System Performance at PT. XYZ - Febryanto, Indra Dwi; Fahlevi, Rezza Agung (UNIPA PRESS, 2025)
PT. XYZ is a company that does business in paper production, one of the revolutions in the field of network distribution based on Internet technology. E-SCM technology has many advantages such as optimizing data recording, and data distribution and facilitating remote monitoring of data systems using WAN Network Topology. Based on the results that have been analyzed, a supply chain management model is needed that can help monitor data systems using WAN network topology distribution that can be accessed by PC Server to the intended International WAN Access.